Thin-rib and high aspect ratio non-stochastic scaffolds by vacuum assisted investment casting - Carneiro, Vítor Hugo Pimenta (2019)
Cellular structures are a classic route to obtain high values of specific mechanical properties. This characteristic is advantageous in many fields, from diverse areas such as packaging, transportation industry, and/or medical implants. Recent studies have employed additive manufacturing and casting techniques to obtain non-stochastic cellular materials, thus, generating an in situ control on the overall mechanical properties. Both techniques display issues, such as lack of control at a microstructural level in the additive manufacturing of metallic alloys and the difficulty in casting thin-rib cellular materials (e.g., metallic scaffolds). To mitigate these problems, this study shows a combination of additive manufacturing and investment casting, in which vacuum is used to assist the filling of thin-rib and high aspect-ratio scaffolds. The process uses 3D printing to produce the investment model. Even though, vacuum is fundamental to allow a complete filling of the models, the temperatures of both mold and casting are important to the success of this route. Minimum temperatures of 250 °C for the mold and 700 °C for the casting must be used to guarantee a successful casting. Cast samples shown small deviations relatively to the initial CAD model, mainly small expansions in rib length and contraction in rib thickness may be observed. However, these changes may be advantageous to obtain higher values of aspect ratio in the final samples.